Lung function testing according leptin levels in patients with chronic obstructive pulmonary disease - Radchenko, O.; Pylypiv, L.; Zukow, W. (Journal of Education, Health and Sport, 2017)
Chronic obstructive pulmonary disease (COPD) belongs to urgent medical and social problems of our time. Prognosis of COPD is often determined by a comorbidity, in particular obesity. The key chain, which unites COPD and obesity, is systemic inflammation, in the development of which the hormone of fatty tissue leptin plays an important role. The presence of receptors to leptin in the alveolar and bronchial epithelial cells, in smooth muscle tissue and submucous bronchial membrane allowes to assume that leptin takes pathogenetic part in COPD progression. The aim of our research was to estimate the leptin level in COPD patient and analyze changes of the respiratory function depending on it. Methods. We have been examined 26 patients with exacerbation of COPD (13 male and 13 female, 58 y.o.) and 20 healthy people representative by gender, age and body mass. The level of serum leptin has been defined by the solid phase enzyme linked immunosorbent analysis, lung function – by computed testing. Results and conclusion. With the leptin level increase all of the lung function parameters progressively decreased, most significant - forced vital capacity and peak expiratory flow. Patients with hyperleptinemia had significantly lower measurements of forced expiratory volume in 1 second and vital lungs capacity. Severe degree of both obstructive and restrictive changes has been found more often among patients with hyperleptinemia and leptin level has been associated with the bronchial obstruction severity.